TERAPI BERMAIN SEBAGAI TRAUMA HEALING PADA ANAK KORBAN BENCANA ALAM KAMPUNG BELENGANG KECAMATAN MANGANITU KABUPATEN KEPULAUAN SANGIHE - Dhito Dwi Pramardika; Jelita Siska Herlina Hinonaung; Astri Juwita Mahihody; Grace Angel Wuaten (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
January 3, 2020, there has been a natural disaster of flash floods and landslides in Belengang village. Much assistance received in the form of food, clothing, health, and other equipment, but there has been no response to disaster victims to trauma, especially in children. If the injury not addressed, it will have a severe impact on the growth and development of these children. Based on that, playing therapy is used as trauma healing. The implementation of this activity carried out in 4 stages, namely the life survey, assessment, preparation, and execution. The results achieved are all children happy, able to socialize with their peers, and more confident.